Diálogos entre a legislação manuelina e o discurso religioso à luz do teatro de Gil Vicente - DUARTE, Andreia Karine (2021)
The dissertation in question has as its main purpose to contribute to the studies of cultural history, related to the Late-medieval period, through the analysis of the texts of Gil Vicente, a Portuguese dramatist who performed several services in the courts of D. Manuel I and D. João III, between the end of the 15th century and the beginning of the 16th. The selected pieces were: Auto da Alma, Auto da Feira, Auto da Barca do Inferno, Auto da Barca da Glória, Romagem dos Agravados and Sermão de Santarém. The main theme verified in these plays refers to social behaviors in Portugal, identified in association with another source, the Manueline Ordinances, a contemporary normative for the dramatist. The work seeks, through a comparative and connective analysis, to confirm that the pieces reflect a double desire for spiritual and temporal powers to restore order and moral behavior. Gil Vicente's pedagogical theater was a great stimulator of social memory, sharing about the “good times” and “good values” to be followed and, as a result, was a strong opponent of the social and behavioral ideals, defended by the humanist movements of the century XVI.